2012
DOI: 10.1177/0047287512457267
|View full text |Cite
|
Sign up to set email alerts
|

Validly Measuring Destination Image in Survey Studies

Abstract: Destination image is among the most frequently measured constructs in empirical survey research. Academic tourism researchers tend to use multi-category scales, often referring to them as "Likert scales," while industry typically uses "pickany" measures. But which leads to results that are more valid? Findings from a large-scale experimental study show that a "forced-choice full binary" format (where respondents have to tick "yes" and "no" for each destination-attribute combination) performs better than both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 19 publications
1
84
0
5
Order By: Relevance
“…Six-point Likert scale (1 denoted fully disagree and 6 denoted fully agree) was used in the questionnaire [100] as earlier research indicated that bipolar 7-point answer scales "took respondents the longest time to complete" ( [101], p. 10; [102]). The first three hypotheses examine the variables of economic (items 1-6), environmental (items 7-12) and socio-cultural (items [13][14][15][16][17][18][19][20] impacts associated with the variables of attitude (items [21][22].…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…Six-point Likert scale (1 denoted fully disagree and 6 denoted fully agree) was used in the questionnaire [100] as earlier research indicated that bipolar 7-point answer scales "took respondents the longest time to complete" ( [101], p. 10; [102]). The first three hypotheses examine the variables of economic (items 1-6), environmental (items 7-12) and socio-cultural (items [13][14][15][16][17][18][19][20] impacts associated with the variables of attitude (items [21][22].…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…The k-means algorithm is prevalent in many of the studies utilizing cluster analysis but its limitations are rarely acknowledged. The use of a structured list of destination attributes for measurement purposes is also heavily criticized [18,50]. Stepchenkova and Mills [45] highlight the need for newer methods to understand destination image.…”
Section: Image Segmentationmentioning
confidence: 99%
“…Chinese tourists are attracted by the perceived "cleanliness" of Europe compared to China and the region's perceived pristine environment can be effectively used for destination advertising and promotion in China. Overall these attributes contribute to a positive destination image that may influence destination preference, tourists' intention to visit, and recommendation behaviour [18].…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Destination branding has received considerable interest from researchers since the early 1970s (Hunt, 1971;Mayo, 1973;Gallarza et al, 2002;Pike, 2002;Martín and Rodríguez del Bosque, 2008;Dolnicar and Grün, 2013;Stepchenkova and Li, 2014).…”
Section: Introductionmentioning
confidence: 99%